PELATIHAN KEGAWAT DARURATAN PADA PETUGAS SATUAN PELAYANAN REHABILITASI SOSIAL LANJUT USIA (SPRSLU) KABUPATEN GARUT - Rudy Alfiyansah; Eldessa Vava Rilla; Yayat; Gani (LP4M STIKes Karsa Husada Garut, 2020)
First aid is very important as a prevention effort so that something worse doesn't happen. This first aid action in an emergency can be in the form of basic life support (BLS) which consists of several simple techniques that aim to maintain a person's life. The purpose of this training is to increase the knowledge and skills of officers to maintain the lives of the elderly. The method used is the workshop/training method in accordance with the problems faced by the elderly social rehabilitation service unit officers, namely they have not mastered the emergency guidelines correctly. The results obtained from this training are the knowledge of officers before receiving emergency training with a less category of 2 (two) people or 10%, enough for 12 people or 12% and knowledge of officers with good categories of 6 people or 30%. The conclusion of this training is that it is able to increase the knowledge of the Elderly Social Rehabilitation Service Unit officers on the concept of emergency victim assistance, able to improve the skills of youth youth groups in providing basic life support and emergency assistance and able to increase the mental readiness of participants in providing emergency assistance.